2014
DOI: 10.1371/journal.pone.0103776
|View full text |Cite
|
Sign up to set email alerts
|

Fully Human Antagonistic Antibodies against CCR4 Potently Inhibit Cell Signaling and Chemotaxis

Abstract: BackgroundCC chemokine receptor 4 (CCR4) represents a potentially important target for cancer immunotherapy due to its expression on tumor infiltrating immune cells including regulatory T cells (Tregs) and on tumor cells in several cancer types and its role in metastasis.MethodologyUsing phage display, human antibody library, affinity maturation and a cell-based antibody selection strategy, the antibody variants against human CCR4 were generated. These antibodies effectively competed with ligand binding, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…A recent publication also reports the use of cell-based phage display selection to optimize scFv targeting CCR4, although the details are not described. 18 Partially purified Figure 3. Determination of the apparent affinity of Fpro0165 for human FPR1 and cynomolgus FPR1 using Schild analysis of activity in a CD11b upregulation assay using in primary human and cynomolgus neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent publication also reports the use of cell-based phage display selection to optimize scFv targeting CCR4, although the details are not described. 18 Partially purified Figure 3. Determination of the apparent affinity of Fpro0165 for human FPR1 and cynomolgus FPR1 using Schild analysis of activity in a CD11b upregulation assay using in primary human and cynomolgus neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the recently published example of CCR4-expressing cell-based selection of a na€ ıve phage display scFv library, 1.1% of the scFv antibodies screened were specific for CCR4, although only 4 out of these 132 antibodies were unique. 18 For the in vitro affinity maturation of antibodies, however, non-specific background due to the use of cells is likely to be less of an issue since the starting point is an antibody already recognizing the protein of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preclinical experiments we found that Affi-5, a fully human anti-CCR4 antibody with antagonistic activity (described in ref. 19), has antitumor activity in a renal cancer model. Inhibition of CCR4 did not reduce the proportion of CCR4-positive infiltrating leukocytes in the tumor microenvironment but altered the phenotype of the immune infiltrate, affecting in particular the phenotype of myeloid cells and increasing the number of infiltrating NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…2 While modulating antibodies against Class B and C GPCRs, and against transporters and ion channels (e.g., P2£3 and P2£7) with relatively large extracellular domains (ECD), have been reported, [3][4][5] functional antibodies against class A GPCRs and most of the transporters and ion channels with a small extracellular domain and small extracellular loops have been more challenging, and examples of mAbs raised against these targets are rare. 6,7 Hybridoma technology and phage display are 2 technologies commonly used for mAb discovery. For both technologies, antigen is required for immunization and for selection and screenings of antigen-specific clones.…”
Section: Introductionmentioning
confidence: 99%